2022
DOI: 10.2340/jrm.v53.1438
|View full text |Cite
|
Sign up to set email alerts
|

Delayed versus Accelerated Weight-bearing Rehabilitation Protocol Following Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis

Abstract: Objective: To compare accelerated and delayed weight-bearing rehabilitation of anterior cruciate ligament reconstruction regarding clinical outcome measures of knee function (International Knee Documentation Committee Subjective Knee Form (IKDC), Lysholm Knee Scoring Scale, Tegner Activity Scale, and Knee Injury and Osteoarthritis Outcome Score (KOOS)), knee laxity, range of movement, quadriceps, and bone tunnel enlargement. Design: Systematic review and meta-analysis. Methods: Systematic searches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(113 reference statements)
0
7
0
1
Order By: Relevance
“…As the principle aim of the present study was mainly radiographic assessment, it only reports on the radiographic outcomes and does not correlate these findings directly to clinical outcomes. However, the recent meta‐analysis conducted by Fan et al [12] did not reveal statistically significant differences between the WB and NWB group in terms of clinical scores such as Lysholm, Tegner, and KOOS. Only the subjective IKDC score exhibited higher values in the WB group.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As the principle aim of the present study was mainly radiographic assessment, it only reports on the radiographic outcomes and does not correlate these findings directly to clinical outcomes. However, the recent meta‐analysis conducted by Fan et al [12] did not reveal statistically significant differences between the WB and NWB group in terms of clinical scores such as Lysholm, Tegner, and KOOS. Only the subjective IKDC score exhibited higher values in the WB group.…”
Section: Discussionmentioning
confidence: 95%
“…The importance of evaluating the post-operative WB has also been previously the subject of intense debate [ 12 , 16 , 36 38 ]. In recent years, there has been a consensus in favour of early WB for these patients, as numerous studies have demonstrated its positive impact on clinical outcomes, resumption of daily activities, and return to sports [ 15 , 17 , 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tunnel enlargement has been associated with by several factors, including tunnel location, 18 , 19 type of fixation device, 8 , 12 , 16 biologic factors such as synovial fluid leakage into the tunnel and cell necrosis from drilling, 20 , 21 low-grade infection, 22 accelerated rehabilitation, 7 , 23 , 24 and bone plug position within the tunnel. 1 , 3 , 4 , 9 Among these, bone plug position is a variable, which can be adjusted during the operation.…”
Section: Introductionmentioning
confidence: 99%